A variável tempo na produtividade bancária: uma pesquisa nas agências de varejo de um grande Banco Brasileiro em Porto Alegre (RS) - Silva, Edinalva Piedade Gouveia da (Universidade do Vale do Rio dos Sinos, 2020)
The time management in companies becomes increasingly important, since emergency can arise at any time. This dissertation aims to create a methodological proposal for the development of a productivity management artifact, relating the use of the time variable in the banking environment, based on the survey and understanding of factors of high influence on productivity. It is the exploitation of a valuable and sometimes neglected resource in highly complex, volatile and competitive environments. Based on this assumption, we sought to understand how time management can impact the experience of customers and organizational results in the context of digital transformation. The work developed relates TOC and VBR theories integrating fields of knowledge to map the critical success factors and the necessary conditions in the enhancement of resources, using the implications found as strategies in creating value for competitive advantage. In this regard, concepts of the Value Chain, Knowledge Management and Performance Indicators were sought, aiming to add quality to the services delivered and qualifying the decisions about important activities to the company's “core business”. The investigation of actions, routines, organizational and decision-making processes, made it possible to relate the existing techniques of Time Management to the management of tangible and intangible assets for the integration of management tools, in a clear and agile communication line, allowing greater autonomy, focus and commitment to priorities for increasing productivity. In the development of this research, there was interaction with service operators at different hierarchical levels of the organization, requirements were raised and based on these definitions, the search for the theoretical framework to support the project was carried out, studying methodologies, tools and related techniques. a Time management. The proposed methodology is not limited to the banking sector, and its applicability may be extended to other microsystems. It is an exploratory, quantitative and qualitative research. The analysis construction path was defined by applying the steps of the Design Science Research (DSR) methodology, building an artifact from the theoretical framework, which allowed the materialization of the actions provided for in the research protocol and considering the factors of influence on productivity, the strategic map and drawn screens, thus creating a methodological process to support the execution of strategic planning, communicating expectations, reducing bureaucracy, raising the learning curve and efficiency for sustainable results.
Keywords: Ferramentas gerenciais; Gestão do tempo; Produtividade; Manegement tools; Time management; Productivity; ACCNPQ::Ciências Sociais Aplicadas::Administração